Performance evaluation of ORC system using evacuated flat plate Photovoltaic-Thermal collector as an evaporator. (December 2021) - Ahmad Qureshi, Izaz; Waqas, Adeel; Ali, Majid; Mehmood, Aamir; Javed, Adeel
Highlights: Low temperature saturated solar organic Rankine cycle (ORC) utilizing evacuated flat plate photovoltaic-thermal (EFPV-T) as evaporator. Investigation of the solar collector's absorber plate temperature and its influence on the efficiency of PV cells that are covering the top surface of the absorber plate. Investigation the performance of solar collector (as evaporator for ORC system) for simple FPC, FPV-T and EFPV-T collector configurations. Mathematical modelling of the Evacuated flat plate collector as the evaporator for the Low temperature saturated solar organic Rankine cycle. Abstract: Low temperature saturated solar organic Rankine cycle (ORC) utilizing evacuated flat plate photovoltaic-thermal (EFPV-T) collector as an evaporator is investigated. A detailed mathematical model for the novel solar thermal collector and ORC has been worked out for the performance analysis of the proposed system. The system is comprised of, stationary solar thermal collector working as an evaporator and other conventional ORC components. A subcritical cycle is considered, and saturated vapor obtained at the solar collector outlet expands in the expander producing useful shaft power. Solar collector's collection efficiency, PV conversion efficiency, Rankine cycle efficiency, system's thermal efficiency, and net power output for 5 working fluids have been comparatively investigated at five different pressure ratios (PR) and in three different collector's configurations including Evacuated Flat Plate Photovoltaic-Thermal Collector (EFPV-T)). Simulation outcomes revealed that solar collector's performance dropped in FPV-T collector's configuration while it significantly improved in the case of EFPV-T configuration consequently enhancing the ORC system's thermal efficiency. The results also revealed that at the same pressure ratio, the fluid with low evaporation temperature will result in better PV performance because the corresponding collector's absorber plate temperature will be lower. Based on the system's overall performance, fluid R245fa appears to be a suitable candidate and exhibited system's overall electrical output of 76.81 W/m 2 and overall electrical efficiency of 8.24%, followed by R601 with a system overall power output of 75.97 W/m 2 and overall electrical efficiency of 8.13%, at 3.5 pressure ratio in EFPV-T collector's configuration.